Simple Mathematics : Interactive Mobile-Based Application Using Augmented Reality Targeting DHH Children - Beverly Dayang, Nathan; Suriati Khartini, Jali; Mohamad Imran, Bandan; Jonathan, Sidi; Nurfauza, Jali (2021)
The idea of the Simple Mathematics Mobile Application using Augmented Reality targeting Children with Hearing Disability is to help children with hearing disability to learn Mathematics in a more visually interactive approach. As we know, Mathematics is an essential subject; therefore, Mathematics is a compulsory subject taught in schools. This is no exception to Special Education schools in Malaysia. However, the method of teaching children with this disability is different from normal children. The different method of teaching children with hearing disability requires a lot of patience as each child have different types of hearing disability. Teachers teaching these children will need special materials that can help the children learn and understand the subject. With the advancement of technology, interactive education is available everywhere. Interactive education integrates computer technology in the classroom that gives a more engaging and fun learning experience for children. Simple Mathematics Mobile Application using Augmented Reality targeting Children with Hearing Disability offers 2 learning languages which are English and Malay Language.